1996
DOI: 10.1111/j.1440-1746.1996.tb00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Review: Regulation of liver regeneration by pro‐inflammatory cytokines

Abstract: The liver has tremendous regenerative capacity. This distinguishes it from other vital organs (e.g. the brain, heart and lungs) that cannot replace functional tissue once it has been destroyed. Although hepatocytes rarely proliferate in the healthy adult liver, virtually all surviving hepatocytes replicate at least once after 70% partial hepatectomy. Therefore, partial liver resection has been used to characterize mechanisms that regulate liver regeneration. Residual hepatocytes up-regulate both proliferative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
8

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 34 publications
3
38
0
8
Order By: Relevance
“…This finding is consistent with other reports of an inability to detect changes in TNF protein levels after PH despite observing induction of mRNA for this cytokine (40,58). One possible explanation is that TNF is acting in a paracrine manner as has been previously suggested by Diehl and coworkers (59,60). Because we did not see a block or delay in DNA replication associated with the lack of Tnf induction in Myd88 KO mice, our results suggest that TNF may not be necessary for regeneration.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding is consistent with other reports of an inability to detect changes in TNF protein levels after PH despite observing induction of mRNA for this cytokine (40,58). One possible explanation is that TNF is acting in a paracrine manner as has been previously suggested by Diehl and coworkers (59,60). Because we did not see a block or delay in DNA replication associated with the lack of Tnf induction in Myd88 KO mice, our results suggest that TNF may not be necessary for regeneration.…”
Section: Discussionsupporting
confidence: 82%
“…Other laboratories, including ours, have previously reported that TNF protein levels transiently increase after PH (6,64,65). Moreover, TNF promotes liver growth in vivo and hepatocyte proliferation in vitro (18, 59, 66 -68) and injection of TNF-neutralizing Abs blocks liver regeneration as well as multiple signaling pathways involved in this process (59,60). We also previously demonstrated that Tnfr1 KO have defective liver regeneration after PH and carbon tetrachloride induced injury (6,69).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, a number of sophisticated methods have been devised to culture hepatocytes for a longer period without losing their replicative potential and differentiation capacity; several key substances including various cytokines are required. 21,22,53,54 There is also evidence suggesting the importance of interactions between parenchymal and nonparenchymal liver cells (especially between hepatocytes and stellate cells) during liver regeneration. These studies have created new dimensions for hepatic investigation.…”
Section: Using a Human Hepatoma Cell Line To Study Bile Canaliculusmentioning
confidence: 99%
“…The molecular mechanism for the triggering is currently unknown, but several recent reports may have provided some intriguing hints. 21,22,54 …”
Section: Using a Human Hepatoma Cell Line To Study Bile Canaliculusmentioning
confidence: 99%